EKSPLORASI STRATEGI BISNIS PENDIDIKAN NON FORMAL BIMBINGAN BELAJAR ADZKIA TERHADAP KEPUTUSAN MEMILIH - Nurhandayani, Nurhandayani (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
The purpose of this study was to determine the partial and simultaneous influence of tutor quality variables, tutoring characteristics and promotion on the decision to choose Adzkia Rantauprapat Tutoring. This type of research is descriptive quantitative. The population of this study was 350 people by taking a sample of 78 from the calculation of the slovin formula as well as the simple random sampling technique as a sampling technique. The results showed that the description of Adzkia Tutoring students prefers Super Executive Class and independent initiative or parental support is a separate reason for attending this Bimbel. The results of this study prove that the variables of tutor quality, tutoring characteristics and promotion both partially and simultaneously have a positive and significant influence on the decision to choose Adzkia Rantauprapat Tutoring. Promotion variable is a variable that determines the competitive advantage of Adzkia Rantauprapat Tutoring because in conducting promotions pay attention to frequency, quality, time and accuracy